Recognition of emergency and non-emergency light using MATROX and VB6 - Muhammad, Mohd Nazeri (2007)
In a daily life there is always a problem to an emergency vehicle such as ambulance, patrol car and fire-fighter to pass through traffic light because it was red and it’s disturbing the drive. A camera system that consists of camera as sensor and some other parts that detect an emergency vehicle could solve the problem from blocked by another vehicle. When the camera that is placed at a certain distance from the traffic light detects an emergency vehicle it would sent a data and it will start the system, then it would activate the traffic light to change to green until the emergency vehicle pass through. This project would focus on developing the software for image processing of emergency light. The captured image will be analyzed using blob analysis to identify connection regions of pixel within the image. The result will be displayed on computer screen to indicate the processed image is emergency light or non-emergency light. This project would use a Visual Basic 6 and Matrox where the image will be process and analyze between emergency and non-emergency light.